ANALISIS PENGURANGAN HAMBATAN KAPAL SELAM MINI HIBRIDA DENGAN VARIASI POSISI DAN BENTUK HIDROFOIL - Tubagus Arya Nugraha, (2023)
Hybrid mini submarines are ships that combine the concepts of conventional fast boats, hydrofoils and submarines in one ship. This ship is an innovation ship that has a special mission in maintaining national sovereignty. In this study, the aim of this research was to analyze drag reduction by varying the position and shape of the NACA hydrofoil. The NACA hydrofoil is varied by changing the position of the NACA hydrofoil and adding the variation of the NACA hydrofoil used. The range of variations used is different for each ship mode. Hydrofoil mode has 9 variations of speed, conventional mode has 8 variations of speed and submarine mode has 5 variations of speed. The method used is a CFD simulation using Ansys CFD software. The results of the study revealed that variations in the position of the NACA hydrofoil that are closer together result in smaller drag, and the selection of a NACA hydrofoil with a symmetrical and slender type will optimally reduce ship drag. The drag reduction that occurs in the combination of position and hydrofoil NACA 0012 gives an average reduction of 12.52%. The varied model succeeded in reducing the value of the total resistance of the ship and obtaining variations in the position and shape of the new NACA hydrofoil. Thus, this research provides an understanding of the components of total ship resistance and their characteristics and can contribute as a reference for further research in the context of developing the maritime technology sector.